Faktor yang Berpengaruh Terhadap Produksi Tebu di Kecamatan Pucakwangi Kabupaten Pati - Erna Setiarini; Sri Marwanti; Shofia Nur Awami; Dewi Hastuti (Proceedings Series on Physical & Formal Sciences, 2021)
This study aims to analyze the factors that influence sugarcane production and analyze the allocative efficiency of the use of sugarcane production factors. This research uses descriptive quantitative method. The method of determining the research location was determined by purposive sampling. The number of sugarcane farmer respondents involved was 72 farmers. The data analysis method uses multiple linear regression analysis which is transformed into a production function of the Cobb-Douglas model. The results of the regression analysis show that the factors that affect sugarcane production in Pucakwangi District, Pati Regency are land, phonska fertilizer and labor factors. Meanwhile, the ZA fertilizer factor has no significant effect on sugarcane production. Allocative efficiency of the use of production factors which include land, phonska fertilizer, ZA fertilizer and labor is not efficient.